PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES PESERTA DIDIK KELAS VIII.6 SMP NEGERI 43 PALEMBANG - Desfianti Desfianti (Universitas Negeri Medan, 2020)
Abstract.Increasing English Learning Outcomes Through Learning Models Examples Non Examples Class VIII.6 Students of SMP Negeri 43 Palembang. The fundamental problem in this study is that most of the students in grade VIII.6 at SMP Negeri 43 Palembang do not understand the material for giving instructions, inviting, prohibiting, asking for permission, and how to respond. Starting from the description above, the problem in this study is formulated, namely the formulation of the problem in this study is: